2018
DOI: 10.1016/j.immuni.2018.01.011
|View full text |Cite|
|
Sign up to set email alerts
|

High-Dimensional Single-Cell Mapping of Central Nervous System Immune Cells Reveals Distinct Myeloid Subsets in Health, Aging, and Disease

Abstract: Individual reports suggest that the central nervous system (CNS) contains multiple immune cell types with diverse roles in tissue homeostasis, immune defense, and neurological diseases. It has been challenging to map leukocytes across the entire brain, and in particular in pathology, where phenotypic changes and influx of blood-derived cells prevent a clear distinction between reactive leukocyte populations. Here, we applied high-dimensional single-cell mass and fluorescence cytometry, in parallel with genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
553
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 726 publications
(591 citation statements)
references
References 73 publications
32
553
2
4
Order By: Relevance
“…1d). This separation of disease-associated CNS immune cell populations agrees with a recent single-cell cytometry-based study [34]. Our transcriptome-based cluster analysis of all 944 microglial cells using the RaceID2 algorithm identified ten clusters (C1-C10), of which cells from C4, C8 and C9 mapped mainly to the tail (Fig.…”
Section: Resultssupporting
confidence: 90%
“…1d). This separation of disease-associated CNS immune cell populations agrees with a recent single-cell cytometry-based study [34]. Our transcriptome-based cluster analysis of all 944 microglial cells using the RaceID2 algorithm identified ten clusters (C1-C10), of which cells from C4, C8 and C9 mapped mainly to the tail (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Next, we considered the possibility that monocytes/myeloid cells infiltrating into the CNS of PLPmut mice or compensatorily recruited myeloid cells upon PLX3397 treatment from outside the CNS contribute to the identified resident CD11b+ cells. Flow cytometry showed that the large majority of CD11b+ cells freshly isolated from the CNS of Wt and PLPmut mice were CD45low and Siglec H+ (Figure a), a microglia‐specific marker (Konishi et al, ; Mrdjen et al, ). Using the microglia‐specific antibody against the transmembrane protein 119 [Tmem119 (Bennett et al, )] on optic nerve sections, nearly all CD11b+ cells in the parenchyma were also Tmem119+ in treated and untreated Wt and PLPmut mice, further arguing against a recruitment of nonresident, myeloid cells from outside the CNS (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a number of papers have reported fundamental differences in the genetic profiles of cultured primary microglia compared to their freshly isolated adult counterparts [37] indicating that in vitro, microglia may not achieve a full resting state. Furthermore, it is important to note that microglia in a healthy mouse brain have very low expression of MHCII at baseline [14, 38, 39]. Therefore, it is difficult to know whether the in vitro expression at baseline is due to compensatory transcriptional pathways, intrinsic differences between in vitro and in vivo cells, or baseline biological differences in activation status between WT and CIITA knock-out.…”
Section: Discussionmentioning
confidence: 99%